simplify 5 - 3 (2n - 1)

5 - 3(2n - 1) = 5 - 6n + 3; = 8 - 6n

Question

Asked 2/26/2009 10:54:17 AM

Updated 6/28/2015 7:52:02 AM

1 Answer/Comment

f
(deployads = window.deployads || []).push({});

Rating

8

5 - 3(2n - 1)

= 5 - 6n + 3;

= 8 - 6n

= 5 - 6n + 3;

= 8 - 6n

Added 6/28/2015 7:52:02 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/29/2015 5:56:18 PM]

multiply and simplify 3(4x-1)+2x-6

Question

Not Answered

Updated 7/13/2014 1:12:01 PM

1 Answer/Comment

3(4x - 1) + 2x - 6

= 12x - 3 + 2x - 6

= 14x - 9

= 12x - 3 + 2x - 6

= 14x - 9

Added 7/13/2014 1:12:01 PM

This answer has been confirmed as correct and helpful.

Simplify 8a + ab - a + 2b + 3ab **Weegy:**
8a + ab - a + 2b + 3ab
= 4ab + 7a + 2b
**User:** Simplify 5 (x + 3) - x **Weegy:** 5 (x + 3) - x
= 4x + 15 (More)

Question

Expert Answered

Updated 7/13/2014 1:13:22 PM

0 Answers/Comments

35,942,791

questions answered

There are no comments.